1970
DOI: 10.1002/bscb.19700790505
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse des Thiénopyridines

Abstract: Des thiknopyridones isombres ont ktb obtenues par cyclisation d'isocyanates de (jT-thiCnyl)vinyle, puis transformdes en thiknopyridines correspondantes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The facility of these cyclization reactions, irrespective of the substitution patterns, was somewhat surprising based on existing precedent. As noted in the introduction (Scheme ), there are prior reports of reactions of simple propargylamines reacting with isothiocyanates giving 2‐aminothiazolidines but these earlier methods either rely on Thorpe‐Ingold type acceleration, much more forcing conditions (e.g., heat or microwave irradiation) or require lengthier reaction times in comparison to our observations where a thiazolidine is obtained under exceptionally mild conditions (r.t. for 2 h) . In contrast, Dethe and coworkers have shown that when various propargylamines and isothiocyanates are reacted in DMF with NaOH as base the corresponding imidazothione (cf.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The facility of these cyclization reactions, irrespective of the substitution patterns, was somewhat surprising based on existing precedent. As noted in the introduction (Scheme ), there are prior reports of reactions of simple propargylamines reacting with isothiocyanates giving 2‐aminothiazolidines but these earlier methods either rely on Thorpe‐Ingold type acceleration, much more forcing conditions (e.g., heat or microwave irradiation) or require lengthier reaction times in comparison to our observations where a thiazolidine is obtained under exceptionally mild conditions (r.t. for 2 h) . In contrast, Dethe and coworkers have shown that when various propargylamines and isothiocyanates are reacted in DMF with NaOH as base the corresponding imidazothione (cf.…”
Section: Resultsmentioning
confidence: 99%
“…( E )‐ N ‐Phenyl‐5‐methylidenethiazolidin‐2‐imine (30a): Synthesized following general procedure B, (50 mg, 0.9 mmol), purified by column chromatography (ethyl acetate/hexanes = 1.5:8.5) to afford compound 30a (138 mg, 80 %) as a light‐brown solid. m.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand thieno[3,2-c]pyridine (thpy) has been prepared by a procedure described elsewhere (ELOY et al, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the generation of such skeletone was recorded as a result of the intramolecular cyclization of β ‐ketoacid amide, forming only two thieno[2,3‐ g ]indolizine derivatives . Secondly, a general methodology for the preparation of triheterocyclic compounds has been found by the mesoionic cycloaddition of dipolarophiles to oxazolones and Reissert compounds . Thus, thieno[2,3‐ g ]indolizine derivatives containing ester groups in the pyrrole moiety have been synthesized …”
Section: Introductionmentioning
confidence: 99%